Evaluating the material properties of underfill for a reliable 3D TSV integration package using numerical analysis. (April 2017) - Yoon, Hyungseok; Choi, Kwang-Seong; Bae, Hyun-Cheol; Moon, Jong-Tae; Eom, Yong-Sung; Jeon, Insu
Abstract: The effects of the material properties of the underfill layer on thermal stress and deformation in 3D through silicon via (TSV) integration packages were evaluated through numerical analysis. Sample TSV packages with underfill composed of different silica volume ratios were fabricated. The sample packages were used to measure thermal deformation using a Moiré interferometer. Also, a cross-section from these samples was used for 2D finite element modeling and numerical analysis to obtain its thermal deformation. The experimental and numerical results were compared to confirm the suitability of the numerical technique in this research. A four-chip-stacked TSV integration package, which includes underfill layers of four different silica volume ratios, was proposed and designed. The diagonal part of the TSV integration packages were three dimensionally modeled and adopted for numerical analysis. Among the underfill with different silica volume ratios in the designed packages, a silica volume ratio of around 20% shows the best performance for a reliable flip chip bonding process, effectively minimizing thermal stress and deformation in the package. Highlights: Thermal stresses and deformations in the 3D TSV package were analyzed. Various underfill material properties were considered and evaluated. Around 20% Si volume ratio shows the best performance for the package reliability.